The Mechanical World of Bacteria - Persat, Alexandre (Cell, 2015)
In the wild, bacteria are predominantly associated with surfaces as opposed to existing as free-swimming, isolated organisms. They are thus subject to surface-specific mechanics including hydrodynamic forces, adhesive forces, the rheology of their surroundings and transport rules that define their encounters with nutrients and signaling molecules. Here, we highlight the effects of mechanics on bacterial behaviors on surfaces at multiple length scales, from single bacteria to the development of multicellular bacterial communities such as biofilms.